Evaluation of Multilevel Surgeries in Children With Spastic Cerebral Palsy Based on Surface Electromyography - Li, Sujiao; Luo, Xueqin; Zhang, Song; Tang, Yuanmin; Sun, Jiming; Meng, Qingyun; Yu, Hongliu; Sun, Chengyan (Frontiers in Neuroscience, 2021)
Root mean square (RMS) of surface electromyography (sEMG) can respond to the neuromuscular function, which displays a positive correlation with muscle force and muscle tension under the positive and passive conditions, respectively. The purpose of this study was to investigate the changes in muscle force and tension after multilevel surgical treatments, functional selective posterior rhizotomy (FSPR) and tibial anterior muscle transfer surgery, and evaluate their clinical effect in children with spastic cerebral palsy (SCP) during walking. Children with diplegia (n=13) and hemiplegia (n=3) aging from 4 to 18 years old participated in this study. They were requested to walk barefoot at a self-selected speed on a 15m long lane. The range of the patient’s joint motion (ROM) and sEMG of six major muscles were assessed before and after the multilevel surgeries. The gait cycle was divided into seven phases and muscle activation state can be divided into positive and passive conditions during gait cycle. For each phase, RMS of sEMG amplitude was calculated and also normalized by a linear envelope (10-ms running RMS window). The muscle tension of the gastrocnemius decreased significantly during the loading response and terminal swing (P<0.05), which helped the knee joint to get the maximum extension when the heel is on the ground and make the heel land smoothly. The muscle force of the gastrocnemius increased significantly (P<0.05) during mid-stance, terminal stance and pre-swing, which could generate the driving force for human body to move forward. The muscle tension of the biceps femoris and semitendinosus decreased significantly (P<0.05) during terminal stance, pre-swing and initial swing. The decreased muscles tension could relieve the burden of the knee flexion when the knee joint was passively flexed. At the terminal swing, the muscle force of tibial anterior increased significantly (P<0.05), which could improve the ankle dorsiflexion ability and prevent foot drop and push forward. Thus, the neuromuscular function of cerebral palsy during walking can be evaluated by the muscle activation state and the RMS of EMG, which showed that multilevel surgical treatments are feasible and effective to treat spastic cerebral palsy.